Synthesis, Characterization of Elastic and Electrical Properties of Diamond-like BCx Nano-Phases Synthesized under High and Low Pressures. (9th January 2018) - Zinin, Pavel V.; Nozhkina, Alla V.; Romanov, Roman I.; Filonenko, Vladimir P.; Titov, Sergey A.; Trojan, Ivan; Fominski, Vyacheslav. Y.; Bulatov, Kamil M.; Bykov, Aleksey A.; Kutuza, Igor B.; Anokhin, Alexander; Lomonosov, Aleksey M.
ABSTRACT: This paper presents experimental results on the synthesis of boron rich diamond-like carbon phases (BCx ) obtained by high pressure sintering (s-BCx ) and pulsed laser deposition (PLD-BCx). It has been shown that sintering of a mixture of a powder of micro-diamonds with a powder of boron in the toroid type high pressure device leads to the creation of s-BCx phase with a low resistivity, and high elastic moduli. The PLD-BCx film found to be rigid with the resistivity as low as that of best conductive boron–doped diamond films. It indicates that the presence of B atoms in a laser plasma leads to the formation of sp 3 bonds in the material in the process of chemical sputtering. The combination of unique characteristics can be achieved by changing the ratio B/C.